IDENTIFICATION AND CHARACTERIZATION OF PTEROPLINTHITE MANGROVE FORESTS - Othman, Rashidi (Journal of Architecture, Planning and Construction Management, 2018)
Mangroves are highly beneficial as they have many environmental and social functions. This paper is aimed at identifying the unique characteristics of Pteroplinthite Mangrove Forest which is one of the mangrove types in Peninsular which has never been documented so far. This kind of mangrove can support numerous residents and non-residents species. It is important to find out the abiotic and biotic factors affecting how they perceive with their surroundings. The study is also expected to explore the most intrinsic value of Pteroplinthite Mangrove Forests that can be integrated as a landscape design element. These intrinsic values of this mangrove forest are being manipulated to be integrated into the urban landscape design setting. The data collection involved the observation, site inventory, determination of physicochemical contents of seawater, and collected sample plants and soil that is conducted in two selected areas, namely Pasir Panjang, Port Dickson and Kuala Linggi, Melaka. The main finding shows the analysis of abiotic and biotic factors of pteroplinthite mangrove that have their own potential and there have eight of intrinsic characters that had been highlighted in the both selected areas of this mangrove forest. It is hoped that this paper may provide significant information on the characteristics of pteroplinthite mangrove forests towards understanding the ecological or functional values of Pteroplinthite mangrove forest habitat as potential approach to be integrated in landscape ecology to restore their habitats and plant species from becoming threatened or extinct.